Subjetividade e ontologia materialista: articulações teóricas entre psicologia e marxismo - Morais, Amom Rodrigues de (2017)
The purpose of this text is to study the relationship between psychology and Marxism in relation to the concept of subjectivity. It intends to explore the materialist ontology of the social being developed by György Lukács, seeking grounds for a materialist historical approach to subjectivity. Thus, in a first moment, aspects of the development of the subjective experience in the modernity, related to the historical constitution of the scientific psychology, are approached. Next, we present contributions from Marxism to the study of subjectivity, in addition to the summary of some psychological theories that have articulated with Marxism. It addresses, in addition, Marxist currents that worked with the subjectivity category. This discussion points out that in the sociability of capitalism, categories of absorption of the sensitive experience undergo transformations which, in turn, require adjustments of scientific knowledge. The impasse lies in identifying if this epistemic matrix, on which Psychology is based, is sufficient to apprehend the totality of the complex of subjectivity and to point out the margin of its transformation. With this, we pass to a second moment, in the interpretation of a systematic part of the Ontology of the social being. In his first chapter, an overview of the work and time of Lukács, the roots and main motivations that preceded the elaboration of his Ontology, is presented. Next, we present an analysis of the relation between subjectivity and the ontological centrality of the work, which indicates to a theory of materialist ontogenesis of the subject. In this sense, subjectivity is this new ontological sphere that exerts force in the categorial unfolding of social reality. Finally, we analyze the chapter of social reproduction, which represents the amplified reproduction of subjectivity at a more complex, more mediated and richer level. In this way, the main contribution of the social ontology of being is to offer a philosophy of the immanence of subjectivity that manifests itself in the history of the transformation of the world of men.